Engineering the Local Coordination Environment and Density of FeN4 Sites by Mn Cooperation for Electrocatalytic Oxygen Reduction. Issue 18 (1st April 2022) - Cai, Huizhu; Zhang, Guanghui; Zhang, Xiao; Chen, Bingbing; Lu, Zheng; Xu, Huajian; Gao, Rui; Shi, Chuan
Abstract: Single atom sites (SAS) of FeN4 are clarified as one of the most active components for the oxygen reduction reaction (ORR). Effective strategies by engineering the local coordination environment and site density of FeN4 sites are crucial to further enhance the electrocatalytic ORR performance. Herein, the integration of a second metal of Mn with Fe to construct Fe&Mn/N‐C catalysts with enhanced density of FeN4 active sites and modulated electronic structure is reported. The formation of MnN4 centers modulates the local environment of FeN4 sites and reserves more FeN4 embedded in carbon substrate by forming the possible FeN4 ‐O‐MnN4 configurations. Density functional theory calculations demonstrate that the overall energy barrier of ORR is decreased over the FeN4 ‐O‐MnN4 moieties. Therefore, the Fe&Mn/N‐C catalyst exhibits enhanced ORR performance both in alkaline and acidic solution (half‐wave potentials are 0.904 and 0.781 V). This work provides an effective strategy by modulating the local electronic structure and density of FeN4 active sites to improve the ORR activity and stability through Mn cooperation. Abstract : Fe&Mn/N‐C catalyst exhibits better oxygen reduction reaction (ORR) activity than Fe/N‐C sole‐component catalyst both in alkaline and acidic media. Enhanced density and modulated electronic structure of FeN4 sites are induced by Mn cooperation. The bridged structure of FeN4 ‐O‐MnN4 configuration is proposed with lower energy barrier in ORR.